Value-added tax on electronic services : a study of the South African tax model - Gopal, Amit Rajendra (Department of Finance and Tax, 2017)
As a general guiding principle, the Commissioner of the South African Revenue Service (SARS) is mandated to collect all tax that is legally payable. This should be done in the most efficient and effective manner, which creates certainty for the taxpayer, reduces the likelihood of tax leakages as far as possible, and should not envisage inhibition of trade. Value-Added Tax (VAT) is a consumption tax aimed at taxing the consumption of goods and services in South Africa. The mechanism where services supplied by non-residents are taxed within a taxing jurisdiction, is more commonly referred to as the imported services/reverse charge mechanism. As consumers seldom use these provisions to accurately account for VAT on purchases made, the legislature decided to introduce new rules governing the supply of electronic services by a foreign supplier to South Africa to level the playing field between foreign and local service providers. The 2013 amendments to the VAT Act, which introduced the treatment of the supply of electronic services, provides focus on a tax specific element of imported services as a local supply. This inherently places certain compliance requirements on foreign suppliers to account for and pay tax to the South African Revenue Service (SARS) where certain electronic services are supplied to consumers in South Africa. These legislative amendments took the initial step to ensure that revenue to the fisc was not being lost by implementing provisions that could keep pace with the rapid growth and development of technology globally. About six months after the introduction of the South African model, the European Union sought to address the same concerns by introducing its own version of these provisions to tax certain electronically supplied services. Both efforts have been successful to date and while the implementation of the South African model is just under three years old, the provisions already seem too narrow and dated when applied to current technological trends. This dissertation has considered the electronic services provisions for both jurisdictions with a view of understanding how the models work, and to identify potential amendments and recommendations which could be applied in the South African context in future (i.e. "Version 2.0"). Based on the research concluded, the opportunity to increase the tax base by broadening the electronic services provisions in South Africa cannot be missed by SARS and National Treasury and while the South African electronic services model may not be perfect, it has significantly changed the space of digital taxation and is one of the pioneers in this field of taxation. While there is still much change that needs to be brought to the current legislative provisions, the initial attempt by SARS and National Treasury is laudable as they have managed, in most instances, to address key concepts with simplified rules and relaxed provisions in order to make the provisions work within the current framework. It is submitted that this bodes well, as an indication to a more vibrant future for the taxation of electronic services in South Africa.